1995
DOI: 10.1126/science.7754368
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of Xenopus Ectoderm into Neurons by NeuroD, a Basic Helix-Loop-Helix Protein

Abstract: Basic helix-loop-helix (bHLH) proteins are instrumental in determining cell type during development. A bHLH protein, termed NeuroD, for neurogenic differentiation, has now been identified as a differentiation factor for neurogenesis because (i) it is expressed transiently in a subset of neurons in the central and peripheral nervous systems at the time of their terminal differentiation into mature neurons and (ii) ectopic expression of neuroD in Xenopus embryos causes premature differentiation of neuronal precu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
799
2
12

Year Published

1997
1997
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 994 publications
(838 citation statements)
references
References 95 publications
25
799
2
12
Order By: Relevance
“…17 NeuroD is expressed transiently in developing neurons in the central and peripheral nervous systems but is not expressed in nearby neuronal progenitors that are still undergoing cell division. 18 mASH1 is required at an early stage in neuronal differentiation and initiates a differentiation program involving NeuroD. 19 It is reported that hASH1 is expressed selectively in normal fetal pulmonary neuroendocrine cells 20 as well as in pulmonary large cell neuroendocrine carcinoma (56.7%) and small cell carcinoma (71.8%).…”
Section: Discussionmentioning
confidence: 99%
“…17 NeuroD is expressed transiently in developing neurons in the central and peripheral nervous systems but is not expressed in nearby neuronal progenitors that are still undergoing cell division. 18 mASH1 is required at an early stage in neuronal differentiation and initiates a differentiation program involving NeuroD. 19 It is reported that hASH1 is expressed selectively in normal fetal pulmonary neuroendocrine cells 20 as well as in pulmonary large cell neuroendocrine carcinoma (56.7%) and small cell carcinoma (71.8%).…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, ectopic RA (or RAR agonists) has significant effects on the anterior ectodermal development, including on anterior endodermalectodermal contacts (e.g., Lee et al, 1995;Kuratani et al, 1998;Escriva et al, 2002;Matt et al, 2003). Matt et al (2003) showed that by using a RAR␤ specific agonist the BA defects associated with RA tetratogenesis were largely replicated; they also applied the agonist to mice carrying a RA-responsive element (RARE) that normally gives expression only up to the second pharyngeal pouch and found reporter expression throughout the APE.…”
Section: Legacy For the Anterior Pahryngeal Endodermmentioning
confidence: 99%
“…XNeuroD, an atonal homologue closely related to Xath5, does not promote expansion of Xomp2 expression when overexpressed, even though it is very effective at promoting ectopic neurogenesis (Lee et al, 1995). Paradoxically, we have previously shown that overexpression of XNeuroD causes an expansion of Xath5 expression in anterior of the embryo (Kanekar et al, 1997), raising the question of why Xath5 promotes expanded Xomp2 expression when overexpressed by RNA injection, but not when its expression is activated after XNeuroD overexpression.…”
Section: Xath5 Can Regulate Olfactory Neurogenesismentioning
confidence: 94%
“…The following constructs were used in probe synthesis: pBS-X-NgnR-1 (Ma et al, 1996), pBS-Xath5 (Kanekar et al, 1997), pBS-Xath 3 (Turner and Wein-traub, 1994), pBS-XNeuroD (Lee et al, 1995), pBSXebf2, pBS-Xebf3, pBS-N-tubulin (Chitnis et al, 1995), and pBK-CMV-Xomp2 (Rossler et al, 1998; gift from H. Breer). Digoxigenin-labeled antisense RNA probes were synthesized in vitro per manufacturer's instruction with a Maxiscript kit (Ambion).…”
Section: In Situ Hybridizationmentioning
confidence: 99%
See 1 more Smart Citation